Explaining the Stunted Rise of Macroprudential Regulatory Philosophies - Baker, Andrew (Politik, 2013)
In the aftermath of the nancial crash of 2008, policy makers operating in international nancial regula- tory networks discovered macroprudential regulation (MPR) and ‘systemic risk’. Macroprudential ideas rose to prominence quite rapidly in the aftermath of the nancial crash of 2008, but the process of translating these ideas into concrete regulatory practice has proceeded slowly and incrementally. e article sets out to explain why this has been the case citing ve factors that have been responsible for stunting the development of macroprudential regulation.